Character Education Patterns Through Validation of the Value In Action For Civics Education Student (VIA-CES) Based distance learning - Sari, Devita Puspa; Sapriya (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
This paper will explain how Citizenship Education teachers develop character education patterns through self-report questionnaires through distance learning-based VIA-CES validation programs. During the covid-19 emergency, there is a new policy of home learning system that requires face-to-face learning to be diverted to distance learning system by utilizing online communication media. This condition becomes a challenge in the actualization of character education through learning. As a supporting factor in producing good citizens, this paper plays an important role in considering how the ideal special pattern to be applied by Citizenship Education teachers in the implementation of character education through self-report questionnaires with distance learning-based VIA-CES validation methods. In the process, this research will use qualitative methods with a case study approach to discover the peculiarities of how character education development patterns are designed based on the study of concepts, procedures, and implementation. The data source of this study was taken from seven informants consisting of a teacher as a key informant, three students, and three parents as supporting informants. Analysis of research data will be obtained from the observation process, indepth interviews with all informants, and document analysis. The results of this study showed an analysis of the implementation of the VIA-CES program on the character development of learners. It has been found that learners can display a wide variety of positive characters according to the indicators presented. This is evidenced by the suitability of the questionnaire report with the circumstances in the field based on confirmation from the observation of parents. Keywords: Character, Civics Education, Distance Learning